Analisis Sentimen Objek Wisata Di Kabupaten Banggai Laut Menggunakan Metode Naive Bayes - Fatmawati; Husdi; Kartika Chandra Pelangi; Rofiq Harun (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2024)
Abstract - are carried out and a place to have fun for a long time to achieve satisfaction, enjoy good service, and bring home beautiful memories of the tourist attractions. In Banggai Laut Regency, many tourist attractions are attractive for tourism activities. The number of visitors increases every year. The discussion about tourist attractions in Banggai Laut Regency is interesting to the local community. There are a lot of public comments about the tourist attractions in Banggai Laut. The number of opinions about tourist attractions in Banggai Laut makes it difficult to determine the sentiment of the comments manually. Therefore, sentiment analysis is required to classify the comments and whether or not they tend to be positive. In this case, this study employs the Naïve Bayes algorithm to classify the problems. Based on the sentiment analysis, it is proven that the Naïve Bayes method or algorithm can classify comments with good results. The accuracy generated in this sentiment analysis is 87%, with a division of training data of 90% and test data of 10%. The acquisition of these accuracy results indicates that the proposed algorithm has a Fairly Good diagnostic level. Keywords: sentiment analysis, tourist attraction, Naïve Bayes